Dermatofibrosarcoma protuberans with PDGFD rearrangements: a case series featuring a novel EMILIN1::PDGFD fusion and comprehensive literature review - Sotiriou, Sotiris; Chatzopoulos, Kyriakos; Charville, Gregory W; Bean, Gregory R; Michal, Michael; Gross, John M; Bridge, Julia A; Gardner, Jerad M; Agaimy, Abbas; Ng, Tony L; Cloutier, Jeffrey M; Saoud, Carla; et al. (Virchows Archiv, 2025)
Dermatofibrosarcoma protuberans (DFSP) is a locally infiltrative mesenchymal neoplasm usually characterized by a COL1A1::PDGFB fusion. A minority of DFSPs have recently been shown to harbor alternative fusions, involving the PDGFD gene. The aim of this case series and literature review is to highlight the clinicopathologic and molecular features of PDGFD-rearranged DFSPs. Eighteen patients (twelve females and six males) with PDGFD-rearranged DFSPs were collected from the authors' institutional archives. Eight (44%) cases harbored a COL6A3::PDGFD fusion, five (28%) an EMILIN2::PDGFD fusion, and two (11%) an EMILIN1::PDGFD fusion. In three (17%) cases, the fusion partner was unknown. A literature review revealed 29 additional cases. Cumulatively, four alternative fusion genes have been detected: COL6A3::PDGFD (24/47, 51%), EMILIN2::PDGFD (12/47, 26%), EMILIN1::PDGFD (2/47, 4%), and TNC::PDGFD (1/47, 2%). In eight (17%) cases, the fusion partner was unknown. Most (20/24, 83%) COL6A3::PDGFD-fused DFSPs occurred in females with only four (17%) cases described in males. Additionally, half of them (12/24, 50%) developed in the breast/chest wall. EMILIN2::PDGFD-fused DFSPs often occurred in males, were located in the extremities (9/12, 75%), exhibited fibrosarcomatous transformation (9/12, 75%), were confined exclusively or primarily to the subcutis (10/12, 83%), and had a well-circumscribed contour (10/12, 83%). Specific molecular alterations in DFSPs correlate with certain clinicopathologic features. Notably, EMILIN2::PDGFD-fused DFSPs have a slight predilection for males, develop almost exclusively in the subcutis, tend to be well-circumscribed, and often exhibit fibrosarcomatous transformation, while COL6A3::PDGFD-fused DFSPs might have a predilection for the breast/chest wall of female patients. To the best of our knowledge, this is the first report of EMILIN1::PDGFD-fused DFSP.
Keywords: DFSP; Dermatofibrosarcoma protuberans; EMILIN1; PDGFD